PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVEING PADA TOKO SK MART DI KECAMATAN JANGKAR - Istiqomah, Laily; Soeliha, Siti; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is one of the most important factors in the company, so it can be said that marketing is the heart in the life of the company. The purpose of this study is to determine the effect of service quality and location on purchasing decisions through consumer satisfaction at the SK mart store. The population in this study were all consumers who came to the SK mart store. The random sampling method (simple probability) pays attention to the strata in the population in this research. In taking this sample using a presentation level of 10%. Data analysis and hypothesis testing in this study used the Structural Equation Model- Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS .3.0 application, indicate that service quality has a significant positive effect on consumer satisfaction, location has a significant positive effect on consumer satisfaction, service quality has a significant positive effect on purchasing decisions, location has a significant positive effect on purchasing decisions, satisfaction consumers have a significant positive effect on purchasing decisions.